1982
DOI: 10.1111/j.1398-9995.1982.tb02334.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Antagonists in Experimental Asthma

Abstract: Verapamil was found to be an effective inhibitor of isometric tension in in vitro, experimental anaphylaxis in guinea pig trachealis smooth muscle. The mean IC50 for protection studies was 2 X 10(-4) M; the drug was also effective as a bronchoreversal agent. The inhibitory effect of verapamil upon the initial rate of isometric muscle tension suggests an action beyond simple calcium channel inhibition. No inhibition of tracheal mast cell histamine release was observed. Verapamil was slightly more potent than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Even though they are weak in blocking the OA-induced contraction in the tracheal smooth muscle, all of them showed a direct relaxing activity on that tissue. Other authors have also demonstrated similar effects on respiratory smooth muscle in-vitro by diltiazem (Nagao et al 1981), by verapamil (Eberlin et al 1982;Weiss et al 1982) and by nifedipine (Drazen et al 1983). Thecontractile activity of respiratory smooth muscle depends on the intracellular calcium provision (Coburn 1977).…”
Section: Discussionmentioning
confidence: 74%
“…Even though they are weak in blocking the OA-induced contraction in the tracheal smooth muscle, all of them showed a direct relaxing activity on that tissue. Other authors have also demonstrated similar effects on respiratory smooth muscle in-vitro by diltiazem (Nagao et al 1981), by verapamil (Eberlin et al 1982;Weiss et al 1982) and by nifedipine (Drazen et al 1983). Thecontractile activity of respiratory smooth muscle depends on the intracellular calcium provision (Coburn 1977).…”
Section: Discussionmentioning
confidence: 74%
“…The results of these trials have thusfar yielded equivocal results [6,7] and there is some uncertainty as to what the mechanism of the beneficial drug-induced bronchodilation might be in asthma. Calcium antagonists either have no ability to block antigen-induced mast-cell or basophil release of histamine, leukotrienes or other inflammatory mediators under in-vitro conditions [8,9,10], or else the blockade requires very high concentrations i.e., 10 -4 M [11,12]. Similarly, a direct bronchodilation caused by these agents in the absence of mediator-induced bronchospasm apparently either does not occur [4,13], or occurs only at high in-vitro concentrations [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a direct bronchodilation caused by these agents in the absence of mediator-induced bronchospasm apparently either does not occur [4,13], or occurs only at high in-vitro concentrations [14]. On the other hand, numerous studies have shown that relatively low concentrations of the calcium antagonists can interfere with vascular and intestinal smooth muscle contractions induced by a variety of autonomic agonists [15] and can inhibit the response of respiratory smooth muscle to diverse inflammatory mediators, including histamine, acetylcholine (ACH) and the leukotrienes [13,14,16] and to various antigens [9,10,13]. Hence, a key mechamsm underlying the effective use of these agents in immune-induced disorders of smooth muscle would seem to be effective blockade of the musculotropic effects of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium antagonists have been reported to exert beneficial (protective) effects in exercise-induced asthma [11 14]. The effects of Ca++-entry blockers on antigen-, histamine-, PGF2~-and methacholine-induced bronchoconstriction in man and animals are highly variable and somewhat controversial [15][16][17][18][19][20][21][22][23][24][25][26][27]38]. Some of the factors that may be responsible for the inconsistent effects of Ca++-channel blockers in immediate hypersensitivity reactions have been outlined in Table 1.…”
Section: Introductionmentioning
confidence: 99%